Building Alien Worlds - The Neuropsychological and Evolutionary Implications of the Astonishing Psychoactive Effects of N,N-Dimethyltryptamine (DMT) - Gallimore, Andrew (Journal of Scientific Exploration, 2013)
<span style="font-size: 11.0pt; line-height: 115%; font-family: "Calibri","sans-serif"; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Times New Roman"; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Arguably the most remarkable property of the human brain is its ability to construct the world that appears to consciousness. The brain is capable of building worlds during waking life, but also in the complete absence of extrinsic sensory data, entirely from intrinsic thalamocortical activity, as during dreaming. DMT, an extraordinary psychedelic, perturbs brain activity such that indescribably bizarre and apparently alien worlds are built. This property of DMT continues to defy explanation. However, by regarding this unique molecule as equivalent to serotonin, an endogenous neuromodulator with a long-standing relationship with the brain, DMT's effects may be explained. Serotonin has evolved to hold the brain's thalamocortical system in a state in which the consensus world is built. When serotonin is replaced by DMT, the thalamocortical system shifts into an equivalent state, but one in which an apparently alien world is built. This suggests that DMT may be an ancestral neuromodulator, at one time secreted endogenously in psychedelic concentrations-a function apparently now lost. However, DMT maintains a number of unique pharmacological characteristics and a peculiar affinity with the human brain that supports this model. Thus, the modern practice of ingesting exogenous DMT may be the reconstitution of an ancestral function.